Report on genotyping for identification of reproductive behaviour in Pm21 using marker assisted selection - Hernández, Luis Miguel; Quintero, Constanza; Castiblanco, Valheria (Bioversity International and the International Center for Tropical Agriculture, 2021)
Continuing with the implementation of the guinea-grass breeding scheme (M. maximus), a half-sibs population was formed through a factorial cross design. Using standardized protocols, the identification of the reproduction mode was carried out in the population of hybrids obtained (called Pm21) using the molecular marker p779 / p780. A total of 3,156 (44%) hybrids, from 6,820, showed the apomictic marker, exhibiting apomixis: sexual ratio of 1: 1. However, among each of the 198 families formed, the apomixis and sexual ratio varied widely.